Inventing the future : a photobiography of Thomas Alva Edison - Delano, Marfe Ferguson; National Geographic Society (U.S.) (Washington, D.C. : National Geographic Society, 2002)
Presents a biography of the tireless Thomas Edison, illustrated with many photos of his life and inventions.
Includes bibliographical references (p. 63) and index.
1140
Accelerated Reader AR
Keywords: Edison, Thomas A. -- 1847-1931 -- Juvenile literature; Edison, Thomas A. -- 1847-1931 -- Portraits -- Juvenile literature; Edison, Thomas A. -- 1847-1931.; Inventors -- United States -- Biography -- Juvenile literature; Electric engineers -- United States -- Biography -- Juvenile literature; Inventors